2020
DOI: 10.1111/jon.12714
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Ticagrelor on Platelet Reactivity in Patients with Clopidogrel Resistance Undergoing Neuroendovascular Procedures

Abstract: BACKGROUND AND PURPOSE: Suboptimal platelet inhibition by clopidogrel (clopidogrel resistance) may be associated with high rates of stent thrombosis and ischemic events. Our objective was to determine if ticagrelor, a P2Y 12 receptor inhibitor, can result in platelet inhibition in patients with clopidogrel resistance. METHODS: A thromboelastography-platelet mapping assay was used in all patients undergoing neuroendovascular procedures requiring oral clopidogrel. In patients with suboptimal platelet inhibition … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 40 publications
0
11
0
Order By: Relevance
“…Due to the lack of appropriate platelet inhibition following clopidogrel administration (clopidogrel resistance), which inhibits the P2Y12 adenosine diphosphate (ADP) receptor and has been associated with higher rates of ischemic complications following neuroendovascular procedures ( 39 ), our institutional approach is to use new P2Y12 antagonists for intracranial stenting, especially for FDs. Although DAPT with acetylsalicylic acid plus clopidogrel is still the main choice for FDs, Podlasek et al recently reported in their meta-analyses that new-generation P2Y12 antagonists (ticagrelor and prasugrel) are safe for patients undergoing flow diversion ( 11 ).…”
Section: Discussionmentioning
confidence: 99%
“…Due to the lack of appropriate platelet inhibition following clopidogrel administration (clopidogrel resistance), which inhibits the P2Y12 adenosine diphosphate (ADP) receptor and has been associated with higher rates of ischemic complications following neuroendovascular procedures ( 39 ), our institutional approach is to use new P2Y12 antagonists for intracranial stenting, especially for FDs. Although DAPT with acetylsalicylic acid plus clopidogrel is still the main choice for FDs, Podlasek et al recently reported in their meta-analyses that new-generation P2Y12 antagonists (ticagrelor and prasugrel) are safe for patients undergoing flow diversion ( 11 ).…”
Section: Discussionmentioning
confidence: 99%
“…A meta‐analysis of 19 published studies with patients undergoing PED for IA did not find preoperative P2Y 12 reaction unit (PRU) values from VerifyNow P2Y 12 assay helpful in guiding reduction of ischemic or hemorrhagic complications, 11 contradicting a previously reported ideal range of 70–150 12 . As for TEG‐PM, one study evaluating the effect of ticagrelor in neuroendovascular patients with clopidogrel resistance used a seemingly arbitrary cutoff value of <60% ADP receptor inhibition to define suboptimal platelet function 13 . Another study assessing TEG‐PM as a reliable platelet function test in neuroendovascular patients identified an optimal percentage ADP receptor inhibition range of 10%–90% 14 .…”
Section: Discussionmentioning
confidence: 99%
“…12 As for TEG-PM, one study evaluating the effect of ticagrelor in neuroendovascular patients with clopidogrel resistance used a seemingly arbitrary cutoff value of <60% ADP receptor inhibition to define suboptimal platelet function. 13 Another study assessing TEG-PM as a reliable platelet function test in neuroendovascular patients identified an optimal percentage ADP receptor inhibition range of 10%-90%. 14 Although TEG-PM has not been proven superior to Ver-ifyNow P2Y 12 assay, our institution prefers TEG-PM as we have found it to be more consistent than PRU values.…”
Section: Discussionmentioning
confidence: 99%
“…Twenty patients were transitioned to oral ticagrelor after exhibiting subtherapeutic adenosine diphosphate (ADP) receptor inhibition defined as ADP inhibition <60%. 13 One patient was allergic to aspirin; therefore, he was placed on cilostazol and clopidogrel. One patient was on aspirin and prasugrel for concomitant cardiovascular disease.…”
Section: Methodsmentioning
confidence: 99%